Rationale and methodology for examining the acute effects of aerobic exercise combined with varying degrees of virtual reality immersion on cognition in persons with TBI - Wender, Carly L.A.; Sandroff, Brian M.; Krch, Denise (Contemporary clinical trials communications, 2022)
Persons with Traumatic Brain Injury (TBI) commonly present with long-term cognitive deficits in executive function, processing speed, attention, and learning and memory. While specific cognitive rehabilitation techniques have shown significant success for deficits in individual domains, aerobic exercise training represents a promising approach for an efficient and general treatment modality that might improve many cognitive domains concurrently. Existing studies in TBI report equivocal results, however, and are hampered by methodological concerns, including small sample sizes, uncontrolled single-group designs, and the use of suboptimal exercise modalities for eliciting cognitive improvements in this population. One particularly promising modality involves the application of environmental enrichment via virtual reality (VR) during aerobic exercise in persons with TBI, but this has yet to be investigated. One approach for systematically developing an optimal aerobic exercise intervention for persons with TBI involves the examination of single bouts of aerobic exercise (i.e., acute aerobic exercise) on cognition. Acute exercise research is a necessary first step for informing the development of high-quality exercise training interventions that are more likely to induce meaningful beneficial effects. To date, such an acute exercise paradigm has yet to be conducted in persons with TBI. To that end, we propose an acute exercise study that will investigate the acute effects of aerobic exercise with incremental degrees of environmental enrichment (VR) relative to a control comparison condition on executive function (divided attention and working memory) and processing speed in 24 people with TBI.